Less is more: Enterobactin concentration dependency in copper tolerance and toxicity - Peralta, Daiana Romina; Farizano, Juan Vicente; Bulacio Gil, Natalia; Corbalán, Natalia Soledad; Pomares, María Fernanda; Vincent, Paula Andrea; Adler, Conrado (Frontiers in Molecular Biosciences, 2022)
The ability of siderophores to play roles beyond iron acquisition has been recently proven for many of them and evidence continues to grow. An earlier work showed that the siderophore enterobactin is able to increase copper toxicity by reducing Cu2+ to Cu+, a form of copper that is more toxic to cells. Copper toxicity is multifaceted. It involves the formation of reactive oxygen species (ROS), mismetallation of enzymes and possibly other mechanisms. Given that we previously reported on the capacity of enterobactin to alleviate oxidative stress caused by various stressors other than copper, we considered the possibility that the siderophore could play a dual role regarding copper toxicity. In this work, we show a bimodal effect of enterobactin on copper toxicity (protective and harmful) which depends on the siderophore concentration. We found that the absence of enterobactin rendered Escherichia coli cells more sensitive to copper, due to the reduced ability of those cells to cope with the metal-generated ROS. Consistently, addition of low concentrations of the siderophore had a protective effect by reducing ROS levels. We observed that in order to achieve this protection, enterobactin had to enter cells and be hydrolyzed in the cytoplasm. Further supporting the role of enterobactin in oxidative stress protection, we found that both oxygen and copper, induced the expression of the siderophore and also found that copper strongly counteracted the well-known downregulation effect of iron on enterobactin synthesis. Interestingly, when enterobactin was present in high concentrations, cells became particularly sensitive to copper most likely due to the Cu2+ to Cu+ reduction, which increased the metal toxicity leading to cell death.